THE CONCEPT OF KNOWLEDGE ACCORDING TO ABDULLAH FAHIM’S EDUCATIONAL THOUGHT - BADRI, KHAIRUL NIZAM BIN ZAINAL (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2021)
The fact of truth or principle that forms knowledge is often seen from three aspects; ontology, epistemology and axiology. In the context of education, ontology is the basis of knowledge that serves to know the nature of divinity, epistemology is the basis of knowledge that serves to explain where science comes from, and axiology is the basis of knowledge that sees the benefits of science. This study seeks to examine the concept of science according to the perspective of Shaykh Abdullah Fahim as a respected educator of his time. In addition, analysis of the link between the basic thoughts on the knowledge and attitude of the Malays towards science will be emphasized. Included in the analysis of the study, are the changes made by Shaykh Abdullah Fahim in developing knowledge. For the purpose of collecting and analyzing data, this study uses an archival approach and fully qualitative methods. The documents examined include the writings of Shaykh Abdullah Fahim which are considered as primary sources and writings about Shaykh Abdullah Fahim are considered as secondary sources. The results of the study found that the concept of knowledge that he conceived is not tied to the traditional stream that pays too much attention to naqli (revealed) knowledge but at the same time not as hard as the islah (reform) stream which places aqli (non-revealed) knowledge as the main basis for development and progress of society.